(untitled) (Research, Society and Development, 2021)
This research aims to demonstrate the relevance of using the therapeutic doll as an educational strategy for the care and prevention of diabetic foot. This is a qualitative action research of an observational nature, with analysis of the articles published in the databases available in the VHL: BDENF; LILACS and SciELO. We developed the workshops providing awareness and awareness of the population about prevention and care with diabetic foot and with great satisfaction we were able to disseminate the results to the community, among other academics and even professionals who knew this approach of active teaching methodology. Finally, we chorus stating that the performance of recreational activities with the elderly is an important ally for strengthening the autonomy of these individuals. It is emphasized the importance of the development of group activities by nurses aimed at the elderly in primary care, mainly for the prevention of disabilities and complications related to chronic diseases, in particular, DM.